Work less, help out more? The persistence of gender inequality in housework and childcare during UK COVID-19 - Zamberlan, Anna; Gioachin, Filippo; Gritti, Davide (Research in social stratification and mobility, 2021)
•The COVID-19 lockdown in the UK caused a strong, general reduction in paid working hours.•Hypotheses based on time availability, relative resources and ‘doing gender’ theories compete about the effect of labour market shocks on the gender division of domestic labour.•We compare similar couples, differing only in lockdown-related loss of paid hours, to investigate the reallocation of time devoted to housework and childcare.•Men and women who lost paid hours during the pandemic dedicated more time to domestic work than individuals who experienced work stability.•We found relevant differences among breadwinners whose paid hours reduced: while men did not significantly change the share of time they spent in unpaid labour, women increased it disproportionately. By leveraging the UK COVID-19 lockdown, this paper examines the impact of changes in paid working hours on gender inequality, specifically time devoted to housework and childcare. We compare potential outcomes of similar couples who only differed in partners’ losing (or maintaining) paid hours during the period from January/February 2020 to April 2020. We draw on wave 9 of the UK Household Longitudinal Study and the first wave of the Understanding Society COVID-19 study to evaluate competing hypotheses derived from time availability, relative resources and ‘doing gender’ perspectives. Following studies on the gendered division of unpaid labour, we also account for heterogeneous implications by analysing couples where partners’ relative contributions to household labour income differ by gender. Our empirical results indicate that both men and women who lost paid hours increased the time devoted to domestic chores, but gender inequality strikes back, especially after breadwinner women lose paid hours. Overall, this paper provides fruitful insights into how theories of gender inequality in the division of domestic tasks could benefit from research on labour market shocks.